2020
DOI: 10.1136/bmjopen-2019-032027
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives of tuberculosis treatment challenges and barriers to treatment adherence in Ukraine: a qualitative study

Abstract: ObjectivesTo understand the challenges faced by patients with tuberculosis (TB) and factors that influence TB treatment adherence in Ukraine.DesignQualitative study.SettingTB treatment facilities in Kyiv Oblast, Ukraine.ParticipantsSixty adults who had undergone treatment for drug-sensitive TB between June 2012 and August 2015.MethodsWe conducted semistructured, in-depth, individual interviews among a purposively selected clinical sample of patients previously treated for drug-sensitive TB. Interview content e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 38 publications
2
23
1
2
Order By: Relevance
“…Three of the eight hospital patients were on DRTB treatment. Age the patients' ranges from 22 to 62 years with a median and inter quartile range of 31 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years. From the analysis of interview transcriptions, 62 codes and five categories emanated which were finally organized into three themes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the eight hospital patients were on DRTB treatment. Age the patients' ranges from 22 to 62 years with a median and inter quartile range of 31 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years. From the analysis of interview transcriptions, 62 codes and five categories emanated which were finally organized into three themes.…”
Section: Resultsmentioning
confidence: 99%
“…The other challenges, experienced by TB patients in the pastoralist community, where economic burden that may expose families of the patients to catastrophic cost [ 10 ]. Due to the inaccessibility of TB service providing health facilities, patients suffer from direct non-medical costs such as transportation cost which can lead to lost to follow up from treatment, [ 27 , 33 ] poor adherence and hence development of DR TB, [ 23 , 34 ] and discourages other patients from seeking care for similar signs and symptoms [ 25 , 26 ]. These challenges can be minimized using different innovative and patient centered approaches such as the use of community treatment supporters [ 28 , 35 37 ], modified self administered treatment methods [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the lack of public knowledge, support from family and health workers as well as the treatment process which takes a long time, so it can increase the risk of transmission by those who have not yet recovered and the possibility of MDR TB in patients who do not adhere to taking medication. The highlight important barriers to TB treatment adherence in this study population and suggest specific interventions that may be beneficial in mitigating high rates of poor treatment 7.…”
mentioning
confidence: 89%
“…12,13 In recent years, although efforts have been made to promote TB care, many patients are still not accessing appropriate health services timely to address their needs. 14 TB patients who experience unmet SCN are more likely to suffer prolonged infection, relapse and even drug resistance. 5,10,11 Additionally, increased evidence has demonstrated that unmet SCN can also lead to a heavy financial burden for TB patients and a waste of medical resources.…”
Section: Introductionmentioning
confidence: 99%